The detergent is circulating in my blood'': a case report - Atmaca, M; Kuloglu, M; Tezcan, E; Unal, A (Taylor & Francis Ltd, 2002)
INTRODUCTION: We report an interesting case of monosymptomatic hypochondriacal psychosis (MHP) which, because of its rarity, tends to be neglected in differential diagnosis. The patient presented with delusions including smelling the odour of detergent and thinking detergent was circulating in his blood. He had many medical and paramedical treatments over 2 1/2 years, and was finally diagnosed with MHP. METHOD: Risperidone was then started, and gradually increased. RESULTS: A significant improvement was observed. However, risperidone was discontinued, because of its hypomanic effects. CONCLUSION: We suggest that risperidone may be an effective alternative treatment in MHP cases, but the hypomanic effects may limit its usefulness.
Keywords: monosymptomatic hypochondriacal psychosis; risperidone; hypomania; hypochondriasis